2021
DOI: 10.1016/j.plefa.2021.102337
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 and omega-6 fatty acids have distinct effects on endothelial fatty acid content and nitric oxide bioavailability

Abstract: Treatment with high dose icosapent ethyl (IPE), an ethyl ester of the omega-3 fatty acid eicosapentaenoic acid (EPA), significantly reduced ischemic events in patients with either cardiovascular disease (CV) or diabetes plus other risk factors (REDUCE-IT) but the mechanism is not well understood. We compared the effects of EPA, docosahexaenoic acid (DHA), and the omega-6 fatty acid arachidonic acid (AA) on bioavailability of nitric oxide (NO) and fatty acid composition. Human umbilical vein endothelial cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 63 publications
3
19
1
Order By: Relevance
“…However, it is known that EPA and docosahexaenoic acid have very different tissue distribution and disparate effects on membrane stabilization and fluidity, formation of cholesterol rafts and crystals, rates of lipid oxidation in lipoproteins and cells, inflammatory modulation, transcriptional regulation, and endothelial function. 47 , 48 , 49 , 50 , 51 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that EPA and docosahexaenoic acid have very different tissue distribution and disparate effects on membrane stabilization and fluidity, formation of cholesterol rafts and crystals, rates of lipid oxidation in lipoproteins and cells, inflammatory modulation, transcriptional regulation, and endothelial function. 47 , 48 , 49 , 50 , 51 …”
Section: Discussionmentioning
confidence: 99%
“…Early studies in patients treated with EPA demonstrated reduced plaque volume, decreased inflammation, increased nitric oxide release, and higher rates of membrane stabilization. [7][8][9][10][11][12][13][14][15] In light of these positive findings, the Reduction of Cardiovascular Events with Icosapent Ethyl (IPE) -Intervention Trial (REDUCE-IT) was designed to explore, in a randomized fashion, the role of IPE in reducing adverse cardiovascular events and whether it too could mitigate ischemic risk to the degree IPE had done in JELIS. 16 The results of the trial were overwhelmingly positive, and since the original publication of the trial, there have been a myriad of subsequent analyses confirming the benefit of IPE in various patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the regulation of vascular tone is not the only function of NO. It is also involved in the regulation of platelet and leukocyte adhesion, thrombosis, and fibrinolysis [ 89 , 90 , 91 ].…”
Section: Cross-links In the Regulation Of Hemodynamics And Innate Imm...mentioning
confidence: 99%